Expression and Function of Aminopeptidase N/CD13 Produced by Fibroblast‐like Synoviocytes in Rheumatoid Arthritis: Role of CD13 in Chemotaxis of Cytokine‐Activated T Cells Independent of Enzymatic Activity. Issue 1 (January 2015) - Morgan, Rachel; Endres, Judith; Behbahani‐Nejad, Nilofar; Phillips, Kristine; Ruth, Jeffrey H.; Friday, Sean C.; Edhayan, Gautam; Lanigan, Thomas; Urquhart, Andrew; Chung, Kevin C.; Fox, David A.
<x xml:space="preserve">Abstract</x> Objective Aminopeptidase N/CD13 (EC 3.4.11.2) is a metalloproteinase expressed by fibroblast‐like synoviocytes (FLS). It has been suggested that CD13 can act chemotactically for T cells in rheumatoid arthritis (RA). We undertook this study to measure CD13 in vivo and in vitro in RA samples and to determine whether CD13 could play a role in the homing of T cells to the RA joint. Methods Interleukin‐17–treated FLS were used to immunize mice, from which a novel anti‐human CD13 monoclonal antibody (mAb), 591.1D7.34, was developed. The mAb 591.1D7.34 and a second anti‐CD13 mAb, WM15, were used to develop a novel enzyme‐linked immunosorbent assay (ELISA) for CD13, and CD13 enzymatic activity was measured in parallel. Chemotaxis of cytokine‐activated T cells was measured by a chemotaxis‐under‐agarose assay. Results We detected substantial amounts of CD13 in synovial fluid (SF), sera, FLS lysates, and culture supernatants by ELISA, with a significant increase in CD13 in RA SF when compared to osteoarthritis SF. CD13 accounted for most but not all of the CD13‐like enzymatic activity in SF. Recombinant human CD13 was chemotactic for cytokine‐activated T cells through a G protein–coupled receptor and contributed to the chemotactic properties of SF independently of enzymatic activity. Conclusion CD13 is released from FLS into culture supernatants and is found in SF. CD13 induces chemotaxis of cytokine‐activated T cells, a T cell population similar to that found in RA synovium. These data suggest that CD13 could play an important role as a T cell chemoattractant, in a positive feedback loop that contributes to RA synovitis.